Preparation of graphene oxide–stabilized Pickering emulsion adjuvant for Pgp3 recombinant vaccine and enhanced immunoprotection against Chlamydia Trachomatis infection - Zhao, Lanhua; Shu, Mingyi; Chen, Hongliang; Shi, Keliang; Li, Zhongyu (Frontiers in Immunology, 2023)
Traditional emulsion adjuvants are limited in clinical application due to their surfactant dependence. Graphene oxide (GO) has a unique amphiphilic property and is a potential surfactant substitute to stabilize Pickering emulsions. In this research, Graphene oxide-stabilized Pickering emulsion（GPE） was prepared and used as an adjuvant for enhanced immune response to Chlamydia trachomatis Pgp3 recombinant vaccine. Firstly, GPE was prepared by optimization of sonication conditions, pH, salinity, GO concentration and water/oil ratio. GPE with small size droplet was characterized and chosen as the candidate. Then, controlled-release antigen delivery by GPE was explored. Cellular uptake behaviours, M1 polarization, cytokine stimulation by GPE+Pgp3 was considered in macrophage. Finally, GPE’s adjuvant effect was evaluated by vaccination with Pgp3 recombinant in BalB/c mouse model. The result showed that GPE with smallest droplet was prepared by sonication under 163 w for 2 min at 1 mg/mL graphene oxide in natural salinity and pH=2 when water/oil ratio was 10:1(w/w). The optimized average GPE droplet size was 1.8 μm and zeta potential was -25.0±1.3 mv. GPE delivered antigens by adsorption them on the droplet surface, showing control release of antigen in vitro and in vivo. In addition, GPE promoted antigen uptake which stimulated proinflammatory TNF-α and inhibited anti-inflammatory IL-10 production, enhancing M1 polarization of macrophages in vitro, and macrophage recruitment was obviously promoted by GPE at the injected site. GPE+Pgp3 induced higher level of IgG, IgG1, and IgG2a production and stimulated more IFN-γ and IL-2 secretion than Pgp3 group, showing a significant Th1-type cellular immune response. C. muridarum challenge showed that GPE enhanced Pgp3’s immunoprotection because of advance clearance of bacterial burden and chronic pathological damage alleviation in the genital tract. This research enabled the rational design of small size GPE, providing explanations from antigen adsorption and control release, macrophage uptake, polarization and recruitment, which enhanced augmented humoral and cellular immunity and ameliorated Chlamydial induced tissue damage in the genital tract.